The effect of bromelain in periodontal surgery: a double-blind randomized placebo-controlled trial - Hossein Babazade; Arad Mirzaagha; Shokoofeh Konarizadeh (BMC, 2023)
Abstract Background Periodontitis is a persistent inflammatory condition. Eliminating the infection and reducing its risk factors are the first steps in treating periodontitis. When the anti-infective therapy is complete, there may still be deep periodontal pockets and prolonged inflammation. Surgical pocket reduction or elimination is indicated under these circumstances. We aimed to evaluate the effect of bromelain on bleeding on probing (BOP), gingival index (GI), and plaque index (PI) after pocket elimination surgery. Methods This double-blind randomized placebo-controlled trial included 28 candidates for pocket elimination surgery referred to the private office of a periodontist in Bandar Abbas, Iran, from April 18 to August 18, 2021. Patients' general characteristics, such as age and sex, were recorded. Additionally, periodontal indices including BOP, PI, GI, and pocket probing depth (PPD) were evaluated in all subjects. All patients underwent pocket elimination surgery. Afterwards, they were randomized into two groups. The first group received 500 mg Anaheal (bromelain) capsules twice a day before meal for one week. The second group received placebo, prepared in similar shape and color by the same pharmaceutical company. BOP, PI, GI, and PPD were assessed four weeks after completion of the treatment course (five weeks after surgery). Results Four weeks after intervention, BOP was significantly lower with Anaheal compared to placebo (0% vs. 35.7%, P = 0.014). However, there was no significant difference in GI between groups (P = 0.120). Mean PI was lower (17.71 ± 2.12 vs. 18.28 ± 2.49) and mean PPD higher (3.10 ± 0.71 vs. 2.64 ± 0.45) in the Anaheal group, but the differences did not reach statistically significant levels (P = 0.520 and P = 0.051, respectively). Conclusions One-week treatment with Anaheal at a dose of 1 g/d after pocket elimination surgery resulted in significantly lower BOP compared to placebo. Trial registration Iranian Registry of Clinical Trials (IRCT), IRCT20201106049289N1. Registered 06/04/2021. Registered prospectively, https://www.irct.ir/trial/52181 .